The efficacy and Safety of Intravesical Bacillus-Calmette-Guerin in the Treatment of Female Patients with Interstitial Cystitis: A double-blinded Prospective Placebo Controlled Study - Irani, Darioush; Heidari, M; Khezri, AA (Urology Journal, 2009)
Purpose: To evaluate the efficacy and safety of intravesical Bacillus Calmette-Gurein injection in the treatment of female patients with interstitial cystitis. Materials and Methods: Thirty women meeting the National Institute of Arthritis, Diabetes, digestive and kidney diseases criteria for interstitial cystitis, were randomized in a double-blinded fashion in two groups each consisted of 15 patients to receive six, weekly instillation of 120 mg BCG vaccine of Iranian Institute of pastor or placebo. Periodic questionnaires on symptoms of interstitial cystitis, voiding diaries, bladder capacity at first desire to void, and maximum bladder capacity were obtained. Adverse events were closely monitored during the treatment and follow-up phases of the study. Subjective and objective baseline values were compared with the follow-up data. Results: With a mean follow-up of 24 (range 6 to 33) months 11 out of 15 (73%) in BCG group, and 3 out of 15 (20%) in placebo group responded to the treatment (P < 0.002). Responders were defined the patients with more than 40% improvement in the symptoms of interstitial cystitis. The global improvement in symptoms and signs of interstitial cystitis was 62%. Adverse events were similar in both groups, mostly irritative in nature and no significant systemic event was noted. BCG did not worsen interstitial cystitis symptoms. Conclusion: We concluded that intravesical BCG is safe, effective, available, and inexpensive with relatively durable results in the treatment of interstitial cystitis.